Integrating Islamic Values and Technology for Holistic Character Education in Indonesian Islamic Schools - Sarwadi Sulisno (Al Hikmah: Journal of Education, 2025)
This study explores a holistic educational approach in Indonesian Islamic schools that integrates Islamic values and digital technology for character development. Employing a qualitative case study at MA Jamilurrahman, data were collected through interviews, observations, and document analysis. Findings reveal that the integration of spiritual, intellectual, emotional, and technological elements fosters ethical and responsible student behavior. The school’s implementation of the Pancasila Student Profile with Rahmatan lil Alamin values demonstrates a contextualized model for Islamic education in the digital age. This study contributes to the development of value-based Islamic education and offers practical insights for curriculum reform.